Fāʿālīyāh Istīkhdām Wāsāʾīl āt-Tāʿlīm ās-Sāwtīyyāh wāā āl-Mārʾīyyāh Sparkol Video Scribe ʿālā Itqānī āl-Mufrādāt āl-ʿArābīyyāh līī āl-Mādrāsāh āl-Ibtidāʾiyyāh - Islami, Diana Fitri; Yasin, Agus; Nur, Ifa Rodifah; Saidah, Ummu; Alfin, M. Fikri Syariati (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2025)
Vocabulary a fundamental component in developing speaking, writing, listening, and reading skills. Without sufficient vocabulary, students find it difficult to express ideas and comprehend spoken or written texts. This issue is particularly evident among students at madrasah ibtidaiyyah, where many learners show limited vocabulary mastery, resulting in difficulties in understanding Arabic texts and participating in classroom interactions. Observations and preliminary data indicate that the use of traditional teaching methods such as rote memorization and textbook-centered instruction has not been effective in engaging students or supporting long term vocabulary retention. These conventional approaches often lack contextualization and fail to stimulate student motivation, making it harder for learners to internalize and apply new words. This study aims to examine the effectiveness of Sparkol Video Scribe, an audiovisual learning media, in enhancing Arabic vocabulary (mufrodat) mastery among Grade 4 students at MI Muhammadiyah 08 Lamongan. The research employed a quantitative approach with a pre-experimental design, specifically a one-group pretest-posttest format. The participants consisted of Grade 4 students, selected from one Islamic elementary school. Data were collected using pretest and posttest vocabulary assessments, and the results were analyzed using the Wilcoxon Signed Rank Test through SPSS software. The findings show that the average pre-test score was 62.73, while the post-test score increased significantly to 96.36. The Wilcoxon test resulted in a significance value of 0.000 < 0.05, indicating a significant improvement in students’ vocabulary mastery after using Sparkol Video Scribe. This study contributes to Arabic language education by proving that audiovisual media can improve vocabulary learning outcomes. Future research is recommended to explore the use of such media in other language skills and on broader populations.